(untitled) (Международный научный журнал «Инженер», 2026)
A railway freight car monitoring system is proposed in which BLE beacons mounted on freight cars transmit data to a stationary network built on Wi-Fi and Power over Ethernet (PoE). BLE beacons (Bluetooth Low Energy) continuously broadcast identifiers and basic telemetry from the cars, while gateway devices (Wi-Fi access points powered via PoE) collect these packets and forward them over Ethernet to a central server. This approach provides high throughput and reliable power for the data collection layer and simplifies network installation by eliminating the need for separate mains wiring. The paper describes the methodology, network architecture, hardware components and server infrastructure. Advantages (broadband capacity, centralized power) and limitations (smaller Wi-Fi coverage area, potential interference in the 2.4 GHz band) of the proposed solution are discussed. Application examples for stations, depots and line sections are considered.